Perspektif Masyarakat Kelurahan Wairotang Terhadap Minyak Kelapa Pintu Air di Pintar Crude Coconut Oil Production Rotat Indonesia - Martina Moy; Sarlina Noni (Jurnal Ilmiah Wahana Pendidikan, 2022)
One of the agricultural sub-sectors that play an important role in the national economy is plantations. Coconut is one of Indonesia's potential plantation commodities. In the Indonesian economy, coconut is one of the strategic commodities because coconut plants have the ability to produce continuously throughout the year. This research is a qualitative research with a descriptive approach, namely the data obtained in the form (words, pictures, behavior) are not stated in the form of numbers or statistical figures but in qualitative form which has a richer meaning than just numbers or frequency. This research was conducted to describe the community's perspective on coconut oil agricultural products from PCP Rotat sluice in Wairotang Village, East Alok District, Sikka Regency. The Wairotang village community has a very high perspective and strongly supports the production of PCP Rotat sluice coconut oil, this can be seen from the routine purchases for consumption purposes. The community's expectation for the Pintu Air coconut oil product at PCP Rotat is that all households in Sikka district will use PCP Rotat coconut oil